Surface Exposure Dating and Geophysical Tomography of the Royal Arches Meadow Rock Avalanche, Yosemite Valley, California - Pacheco, Marcus; Plattner, Alain M.; Stock, Greg M.; Rood, Dylan H.; Pluhar, Christopher J. (Frontiers in Earth Science, 2020)
Since the retreat of glaciers after the Last Glacial Maximum, rock avalanches have occurred intermittently in Yosemite Valley, California. We investigated the distal portion of the oldest of these, the Royal Arches Meadow rock avalanche, which has been partially buried by sediment aggradation. Cosmogenic 10 Be exposure ages of boulders within the deposit indicate that the rock avalanche occurred at 16.0 +/- 0.3 ka, immediately after deglaciation and thus prior to most aggradation. The interface between the rock avalanche deposit and the underlying glaciofluvial sediments therefore provides an elevation marker of the valley floor at the time of deposition. To identify the elevation of this interface, we collected eight Ground Penetrating Radar (GPR) and five Electrical Resistivity Tomography (ERT) profiles across the rock avalanche. Both methods are sensitive to contrasts between the granitic avalanche deposit and the underlying sediments. By constraining ERT inversions with GPR interfaces that are continuous across the profiles, we identified a single interface, interpreted as the basal contact of the rock avalanche, that separates resistive material from conductive material underneath. The elevation of this approximately horizontal interface is between 1,206 m and 1,209 m, roughly 10 m below the modern ground surface, indicating ≈10 m of sediment aggradation since deglaciation. Based on topographic expression and depth to this contact, we determined a minimum volume estimate of between 8.1*10^5 m^3 and 9.7*10^5 m^3 , nearly three times larger than what would be estimated from surface expression alone. Our findings allow reconstruction of the sedimentation history of Yosemite Valley, inform hazard and risk assessment, and confirm that geophysical methods are valuable tools for three-dimensional investigations of rock avalanches, particularly those buried by younger sediments.